MANAJEMEN PUBLIC RELATIONS PT. JASA RAHARJA (PERSERO) CABANG RIAU DALAM MENINGKATKAN IMAGE POSITIF KEPADA MASYARAKAT KOTA PEKANBARU - Dewantoro, Taufik Ilham; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The services carried out by Jasa Raharja which are communicated by some people, they can be used in the community of Pekanbaru City. The purpose of this study was to determine the management of public relations: planning, organizing, staffing, leading and controlling Jasa Raharja Riau Branch, to find out what media was done to determine the inhibiting factors and supporting factors in improving the positive image for the people of Pekanbaru City.The research method used in this study is a qualitative descriptive method by setting 4 (four) research subjects as informants through purposive techniques and the people who are taking care of claims. Data collection techniques used in this study were interviews, observation, and documentation. Data analysis techniques in this study used the interactive data model of Miles and Huberman. Checking data uses the technique of extending participation and triangulation.The results of this study indicate that the management used by Jasa Raharja Public Relations in improving the image was successful. Even though they still get complaints from some people, they understand and the community thinks the image of Jasa Raharja is good. Some of the things that need to be considered by the Riau Jasa Raharja Public Relations in conducting management in terms of planning, organizing, staffing, leading and controlling have gone well even though there are few obstacles in the organizing and staffing section because of the limited available HR. Jasa Raharja Riau branch uses a variety of media in improving its corporate image, the media used are print media, electronic media, social media and websites as well as outdoor media. Jasa Raharja Public Relations of Riau Branch has inhibiting factors and supporters carry out public relations activities in order to improve the image of the people of Pekanbaru City. The inhibiting factor is limited human resources, especially the absence of human resources who do have a public education background. The supporting factors are the fulfillment of adequate facilities and infrastructure for public relations in carrying out activities such as DSLR cameras, computers equipped with the internet, and official vehicles that help mobility public relations in activities.Keyword : Management, Public Relations, Positive Image